Location and Brand Image Outshine Price in Homebuyer Decisions in Indonesia: Lokasi dan Citra Merek Mengalahkan Harga dalam Keputusan Pembeli Rumah di Indonesia - Dian Ramadhani; David Sukardi Kodrat (Academia Open, 2024)
General Background: The increasing population in Medan has led to a rising demand for housing, prompting competition among companies to provide secure and comfortable upper-middle-class residences. Specific Background: Citraland Helvetia serves as a case study to understand the dominant factors influencing consumer decisions in purchasing homes. This study specifically investigates whether price, location, promotion, brand image, and facilities significantly impact the purchase decisions at Citraland Helvetia. Knowledge Gap: Previous research has not conclusively identified which factors are most influential during the product launch phase for residential properties in this region. Aims: This study aims to identify the dominant factors affecting consumer purchasing decisions during the product launch of Citraland Helvetia, focusing on location, brand image, and price. Results: The study found that location and brand image are the two most influential factors in the decision-making process, while price has a significant impact but is not as dominant. Promotion and facilities also positively influence purchasing decisions. Novelty: The research provides empirical evidence highlighting the critical role of location and brand image over price during the initial launch phase, which contrasts with the common perception that price is the primary determinant. Implications: These findings suggest that developers should prioritize strategic location selection and strong brand image development to attract buyers. Enhancing these elements can lead to better consumer satisfaction and potentially higher investment returns. The study's insights can inform future urban development and marketing strategies in the housing sector, particularly in emerging urban areas like Medan. Highlights: Dominant Factors: Location and brand image drive home purchase decisions. Price Impact: Less significant during initial product launch phase. Strategic Focus: Prioritize location and brand image for buyer attraction. Keywords: Housing demand, Medan, Consumer decision, Location, Brand image